2014
DOI: 10.1007/s40145-014-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of reaction layer and its effect on the joining strength of SiC/SiC joints brazed using Ag-Cu-In-Ti alloy

Abstract: Abstract:The SiC/SiC joints were vacuum brazed at 700 ℃, 740 ℃, 780 ℃ and 800 ℃ for 10 min respectively, using Ag-Cu-In-Ti active filler alloy. The microstructure and joining strength of the joints were characterized by electron probe X-ray microanalyser (EPMA), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM) and four-point bending strength test. The interface of the joints was composed of three parts: SiC substrate, reaction layer and filler alloy. A representative microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
(23 reference statements)
3
20
0
1
Order By: Relevance
“…For SiC/SiC joints brazed with Ag‐Cu‐Ti (Cusil ABA), the reaction layer is typically reported to comprise of a TiC layer adherent to the SiC (having a film like morphology) and a Ti 5 Si 3 adherent to the TiC layer (having a scale like morphology) . Similarly for Incusil ABA brazed SiC/SiC joints, a layered structure of the reaction layer was observed by Liu et al, with the addition that a layer mainly rich in In, Si, and Ag (and minor additions of Ti, C and Cu) was found in‐between the SiC interface and the TiC layer. Liu et al proposed that during brazing the TiC‐layer cracks or delaminates allowing liquid braze material to flow into the formed gap and consequently leading to the formation of this additional In‐containing layer (adjacent to SiC).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…For SiC/SiC joints brazed with Ag‐Cu‐Ti (Cusil ABA), the reaction layer is typically reported to comprise of a TiC layer adherent to the SiC (having a film like morphology) and a Ti 5 Si 3 adherent to the TiC layer (having a scale like morphology) . Similarly for Incusil ABA brazed SiC/SiC joints, a layered structure of the reaction layer was observed by Liu et al, with the addition that a layer mainly rich in In, Si, and Ag (and minor additions of Ti, C and Cu) was found in‐between the SiC interface and the TiC layer. Liu et al proposed that during brazing the TiC‐layer cracks or delaminates allowing liquid braze material to flow into the formed gap and consequently leading to the formation of this additional In‐containing layer (adjacent to SiC).…”
Section: Resultsmentioning
confidence: 92%
“…The joining was conducted under vacuum (≤10 −4 mbar). A final brazing temperature of 740°C and a holding time of 10 minutes (Figure D) were chosen as Liu et al reported this is where a maximum of bending strength of SiC/SiC joints as a function of brazing temperature may occur.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations